High pre‐operative serum aminotransferase levels predict local recurrence after curative resection of hepatocellular carcinoma. Issue 1 (23rd April 2014) - Chung, Kun‐Ming; Chien, Tsu‐Ming; Chuang, Shih‐Sung; Wu, Hung‐Chang; Sheu, Ming‐Jen; Lin, Ching‐Yih; Kuo, Hsing‐Tao
Summary: Background: Hepatocellular carcinoma is a common cancer with an increasing incidence worldwide because of the dissemination of hepatitis B and hepatitis C virus infection. Surgical resection is the most important therapeutic option with a curative intent. Early tumor detection through screening and improvements in surgical techniques have significantly improved the outcome of patients with hepatocellular carcinoma. However, local recurrence after curative hepatic resection is common and is the most frequent cause of death in these patients. Patients and Methods: In an attempt to identify the risk factors that predict tumor recurrence, we conducted this retrospective study in a single institution for a 6‐year period. Of the 100 consecutive patients who underwent curative tumor resection, we analyzed age, sex, viral etiology (hepatitis B virus vs. hepatitis C virus), preoperative levels of aspartate aminotransferase and alanine aminotransferase, the α‐fetoprotein level, underlying liver disease status (chronic hepatitis vs. cirrhosis), number and size of tumors, type of resection, and presence of microvascular invasion. Results: In the median follow‐up period of 36 months (range, 12–85 months), the 1‐year, 3‐year, and 5‐year overall survival rates were 90%, 84%, and 73%, respectively; tumor recurrence occurred in 38 (38%) patients and was the leading cause of death among the patients who died (15 of 17 patients; 88%). On univariate analysis, the only factor significantly associated with a higher incidence of tumor recurrence was preoperative levels of aspartate aminotransferase greater than twice the upper normal value ( p  < 0.01) and this factor remained significant with multivariate analysis. Subgroup analysis of the risk factor of early tumor recurrence (≤2 years) and late tumor recurrence (>2 years) was conducted and a preoperative aspartate aminotransferase level greater than twice the upper normal value was still significant in both groups ( p  = 0.02 and p  = 0.044, respectively). Conclusion: Although this is a small‐scale study, our findings could be easily applied clinically and used as readily available indicators to help the follow‐up algorithm. We also suggest antiviral management as soon as possible for patients with hepatocellular carcinoma undergoing curative resection, especially those with a high preoperative aspartate aminotransferase level.